2021
DOI: 10.1101/2021.09.10.21262527
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antibody kinetics to SARS-CoV-2 at 13.5 months, by disease severity

Abstract: Background: Understanding humoral responses and seroprevalence in SARS-CoV-2 infection is essential for guiding vaccination strategies in both infected and uninfected individuals. Methods: We determine the kinetics of IgM against the nucleocapsid (N) and IgG against the spike (S) and N proteins of SARS-CoV-2 in a cohort of 860 health professionals (healthy and infected) in northern Barcelona. We model the kinetics of IgG and IgM at nine time points over 13.5 months from infection, using non-linear mixed mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
1
2
0
1
Order By: Relevance
“…Although incomplete avidity maturation of IgGs targeting SARS-CoV-2 keeps avidity levels low, it seems that with the right selection of "cut-off" values, avidity testing could be helpful in determining the stage of the infection in COVID-19 patients [37]. Our data are in agreement with previous studies that show a decrease in antibody levels several months (3-13.5 months) after infection [17,23,29,39,40], as well as an increase in antibody avidity that reaches a plateau a few months (21 days-8 months) after infection [29][30][31][32]37,[41][42][43]. An added value of the present study is that data have been obtained during a longer time course, up to fifteen months, as compared to previous reports, where antibody avidity was addressed at time-points up to eight months after infection.…”
Section: Discussionsupporting
confidence: 90%
“…Although incomplete avidity maturation of IgGs targeting SARS-CoV-2 keeps avidity levels low, it seems that with the right selection of "cut-off" values, avidity testing could be helpful in determining the stage of the infection in COVID-19 patients [37]. Our data are in agreement with previous studies that show a decrease in antibody levels several months (3-13.5 months) after infection [17,23,29,39,40], as well as an increase in antibody avidity that reaches a plateau a few months (21 days-8 months) after infection [29][30][31][32]37,[41][42][43]. An added value of the present study is that data have been obtained during a longer time course, up to fifteen months, as compared to previous reports, where antibody avidity was addressed at time-points up to eight months after infection.…”
Section: Discussionsupporting
confidence: 90%
“…6 Biomolecular Screening and Protein Technologies Unit, Centre for Genomic Regulation (CRG), The Barcelona Institute of Science and Technology, Barcelona, Spain. 7 Centre d' Atenció Primària (CAP) Sant Joan de Vilatorrada. Gerència Territorial de la Catalunya Central, Institut Català de la Salut, Sant Fruitós de Bages, Spain.…”
Section: Supplementary Informationunclassified
“…We have previously shown that 90% of those infected with SARS-CoV-2 remain seropositive 1 year after discharge [1,2]. To our knowledge, the duration of antibody responses following natural infection has not been assessed beyond 13-20 months to date [3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Paper-based POC immunoassays, particularly LFTs, have received great attention because of the requirement for joint qualitative and quantitative biosensing applications. For the purpose of diagnosing human health, different LFTs have been commercialized for the detection of different markers (Violan et al, 2021). Nanomaterials have been used for the development of POC diagnostics and delivery strategies.…”
Section: Lateral Flow Tests and Covid-19mentioning
confidence: 99%